Hepatic failure and liver cell damage in acute Wilson's disease involve CD95 (APO-1 /Fas) Mediated apoptosis - Strand, Susanne; Hofmann, Walter J.; Grambihler, Annette; Hug, Hubert; Volkmann, Martin; Otto, Gerd; Wesch, Horst; Mariani, Sara M.; Hack, Volker; Stremmel, Wolfgang; Krammer, Peter H.; Galle, Peter R. (Nature medicine, 1998)
Wilson's disease can result in fulminant liver failure due to hepatic copper overload. The CD95 system mediates apoptosis and has been demonstrated to be involved in liver disease. In this study CD95 mediated apoptosis was investigated in patients with fulminant hepatic failure in the course of Wilson's disease and in an in vitro model of copper treated human hepatoma cells. In patients, hepatic expression of CD95 and CD95L mRNA and apoptosis were detected. Copper overload in vitro resulted in hepatocytic apoptosis which could be reduced with a neutralizing anti-CD95L antibody. Copper treatment of hepatocytes results in activation of the CD9S system and induction of apoptosis which is operative during the course of hepatic failure in acute Wilson's disease.